Anti-diabetic activity of crude Pistacia lentiscus in alloxan-induced diabetes in rats (Bangladesh Journal of Pharmacology, 2015)
The purpose of this study was to investigate the anti-diabetic effect of crude Pistacia lentiscus gum (mastic gum) in alloxan-treated diabetic rat model. The crude P. lentiscus (100 mg/kg) showed significant (p